2020
DOI: 10.1093/cid/ciaa1021
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of a Coronavirus Disease 2019 Outbreak in a Nursing Home Through Serial Testing of Residents and Staff

Abstract: Nursing homes and long-term care facilities represent highly vulnerable environments for respiratory disease outbreaks, such as COVID-19. We describe a COVID-19 outbreak in a nursing home that was rapidly contained by using a universal testing strategy of all residents and nursing home staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 9 publications
3
57
0
1
Order By: Relevance
“…This is consistent with reported transmission dynamics of SARS-CoV-2; for instance, modelling studies have estimated that 30-57% of secondary infections among identified transmission pairs resulted from pre-symptomatic transmission [49], and that, early on in COVID-19 outbreaks in Singapore and Tianjin, pre-symptomatic transmission accounted for at least 65% of all transmission events [19]. Findings are also consistent with high proportions of asymptomatic infection, and important roles for presymptomatic and asymptomatic transmission reported in various LTCF outbreaks [5,16,21,[26][27][28][29]. The often silent nature of SARS-CoV-2 transmission highlights epidemiological challenges associated with screening for emerging outbreaks using symptoms alone.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This is consistent with reported transmission dynamics of SARS-CoV-2; for instance, modelling studies have estimated that 30-57% of secondary infections among identified transmission pairs resulted from pre-symptomatic transmission [49], and that, early on in COVID-19 outbreaks in Singapore and Tianjin, pre-symptomatic transmission accounted for at least 65% of all transmission events [19]. Findings are also consistent with high proportions of asymptomatic infection, and important roles for presymptomatic and asymptomatic transmission reported in various LTCF outbreaks [5,16,21,[26][27][28][29]. The often silent nature of SARS-CoV-2 transmission highlights epidemiological challenges associated with screening for emerging outbreaks using symptoms alone.…”
Section: Discussionsupporting
confidence: 56%
“…Insufficient surveillance systems, including those lacking testing capacity or relying only on symptoms as indications for testing, have been identified as aggravating factors for COVID-19 outbreaks in LTCFs [8,16,[24][25][26][27]. Various surveillance strategies have been proposed to optimize testing while accounting for the particular transmission dynamics of SARS-CoV-2, including randomly testing HCWs, testing all patients upon admission, and universal or serial testing [28][29][30]. Yet COVID-19 surveillance is limited in practice by available testing capacity and health-economic resources, particularly for institutions in low-and middle-income settings [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The driving reason for the extreme interventions necessary for outbreak prevention is the overwhelming force of infection on a high-density setting like a cruise ship. Outbreaks in congregate living and other high-density contact environments have been observed, including in prisons, nursing homes, and university dormitories ( 24 , 25 ). Outbreak control has been challenging in these settings because of the need to maintain ongoing social distancing in environments where that is often infeasible.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,14,18,19 Asymptomatic SARS-CoV-2 infections were also identified, with rates from 16% to 69.7%. 9,10,[12][13][14]16,17,19 In studies by Arons et al and Escobar et al, 88-92% of residents with asymptomatic infections developed symptoms during subsequent follow up. 9,12 By contrast, Patel et al and Graham et al reported only 3% to 10% of asymptomatic infections developing subsequent symptoms among nursing home residents.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…9,10,[12][13][14]16,17,19 In studies by Arons et al and Escobar et al, 88-92% of residents with asymptomatic infections developed symptoms during subsequent follow up. 9,12 By contrast, Patel et al and Graham et al reported only 3% to 10% of asymptomatic infections developing subsequent symptoms among nursing home residents. 14,16 Prognosis Following COVID-19 diagnosis, many LTCF residents required subsequent hospitalization or expired ( Table 1).…”
Section: Clinical Presentationmentioning
confidence: 99%